Accounting for the faculty differentials in the production of PhD graduates in a South African university - Tanga, M.; Megbowon, F.; Nkonki, V.; Rulashe, T. (South African Journal of Higher Education, 2021)
The ability of an institution to graduate students, also known as the throughput rate, is one of the most important means of an institution receiving a grant/ subsidy from the government. This article sought to interrogate the differentials in throughput rates of PhD graduates per faculty in a selected institution over a period of five years. Framed within the interpretive paradigm, a qualitative approach and a case study design were adopted. A non-probability purposive sample of 30 participants was selected the academic staff within the six faculties that make up the university under investigation. Data was collected through in-depth interviews and document analysis. Interview transcripts were analysed thematically and using the constant comparison technique. The major findings pointed to differentials in PhD production across faculties as emanating from variations in supervision approaches as reflected in the recruitment and selection of candidates, students’ composition, allocation of supervision load, preparation and orientation of candidates, mentoring of both students and junior staff members, as well as monitoring and evaluation of students’ progress. The findings also revealed challenges like lack of financial support for students, poor structural set-up of some faculties as well as “positive” discrimination in some faculties. These factors constrained the throughput rates in different faculties differently, resulting to a difference in PhD graduate production. It is concluded that there are some quality concerns resulting from the poor processes and procedures as well as the number of graduates from some staff members. It is recommended that the university harmonise its diverse PhD processes and procedures, and enlarge some faculties by creating distinct departments to provide requisite support and interventions to narrow the differentials and improve quality.